The local charge carrier interaction with lattice defects in ZnCdTe and ZnHgTe solid solutions - Malyk, O.P. (Functional Materials, 2009)
The processes of the charge carrier scattering on the short-range potential caused by interaction with polar and nonpolar optical phonons, piezoelectric and acoustic phonons, static strain, neutral and ionized impurities in ZnₓCd₁₋ₓTe (0x1) and ZnₓHg₁₋ₓTe (x = 0.15) are considered. The temperature dependence of the charge carrier mobility in temperature range 50-360 K are calculated. Розглянуто процеси розсіяння носія заряду на близькодіючому потенціалі, викликаному взаємодією з полярним та неполярним оптичними фононами, п'єзоелектричними та акустичними фононами, статичною деформацією, нейтральними та іонізованими домішками в ZnₓCd₁₋ₓTe (0x1) та ZnₓHg₁₋ₓTe (х = 0.15). Розраховано температурні залежності рухливості носія заряду в інтервалі температур 50-360 К. Рассмотрены процессы рассеяния носителя заряда на близко-действующем потенциале, вызванном взаимодействием с полярным и неполярным оптическими фононами, пьезоэлектрическими и акустическими фононами, статической деформацией, нейтральными и ионизированными примесями в ZnₓCd₁₋ₓTe (0x1) и ZnₓHg₁₋ₓTe (х = 0.15). Рассчитаны температурные зависимости подвижности носителя заряда в интервале температур 50-360 К.